Research in the Social Enterprise Journal – from the margins to the mainstream. Issue 1 (5th February 2018) - Doherty, Bob
Abstract : Purpose: The purpose of this paper is to review the development and impact of the Social Enterprise Journal ( SEJ ) from its inception in 2005 until present day. Design/methodology/approach: The paper analyses the thematic content of SEJ and its impact data from 2005 until 2017. Findings: SEJ has broken new ground in the study of social enterprise (SE). It was the first journal back in 2005 to commence the exploration of this field and since has been the first to publish works on defining SE, their performance management, critical perspectives plus international differences. The paper shows that in the early years, SEJ was dominated by conceptual work aiming to understand SE plus their governance and performance management, which was mainly based on UK descriptive case studies and uncritical. By 2010, SEJ became established internationally with various issues being 100 per cent dominated by international aspects of SE. Recent more critical work has also enabled a process of "myth busting" in the SE field. This paper also shows the growth of SEJ in downloads and citations. Practical implications: The paper demonstrates the important role SEJ has played in both improving practice and informing policy. Originality/value: The paper is the first to review the development and impact of SEJ .